1 - The Re-Making of Africa: Ayi Kwei Armah and the Narrative of an (Alter)-native Route to Development - Gbemisola Adeoti (Africa Media Review, 2005)
The paper is a critical exploration of Ayi Kwei Armah’s novels with a view to analysing the author’s perception of and responses to Africa’s contemporary political history. Using The Beautyful Ones Are Not Yet Born (1968) and Osiris Rising (1995) for in-depth study, the paper stresses the trajectory of Armah’s philosophical reflections on ‘the trouble with Africa’ as it relates to governance and development. The study is premised on a theoretical assumption that African literary arts, oral and written, are capable of generating the necessary stimuli for change. In its fictiveness, literature proffers different perspectives of existential problems and their solutions. A politically engaged novel, the type that Armah often writes, is an apt canvas for paradigmatic interactions of contending ideas and social forces.